Composition of Functions
f o g(x)=f(g(x)) --> I know that this is eqivalent to f(g(x))
Given f(x) = 2x+1, and g(X) = 3x+1 find:f o g(x)=f(g(x))
This is what I did, but I don't think Ive solved it correctly
f(g(x)) = f(x-3)
f(x-3) = 1(x-3)-3x+2
f(g(x)) = -2x-1
The perimeter P of a square and the area A of a square r functions of its side length S. write area as function of Perimeter. ?
Also write out the square's area as function of length of its diagonal.
f(g) = 2g+1 = 2(3x+1)+1 = 6x+3
dunno where you got x-3
P = 4s
A = s^2 = (P/4)^2 = P^2/16
d = s√2
A = s^2 = (d/√2)^2 = d^2/2posted by Steve